Super-resolved protein imaging using bifunctional light-up aptamers - Grün, Franziska; Bergh, Niklas van den; Klevanski, Maja; Verma, Mrigank S.; Bühler, Bastian; Nienhaus, G. Ulrich; Kuner, Thomas; Jäschke, Andres; Sünbül, Murat (Angewandte Chemie. International edition, 2024)
Efficient labeling methods for protein visualization with minimal tag size and appropriate photophysical properties are required for single-molecule localization microscopy (SMLM), providing insights into the organization and interactions of biomolecules in cells at the molecular level. Among the fluorescent light-up aptamers (FLAPs) originally developed for RNA imaging, RhoBAST stands out due to its remarkable brightness, photostability, fluorogenicity, and rapid exchange kinetics, enabling super-resolved imaging with high localization precision. Here, we expand the applicability of RhoBAST to protein imaging by fusing it to protein-binding aptamers. The versatility of such bifunctional aptamers is demonstrated by employing a variety of protein-binding aptamers and different FLAPs. Moreover, fusing RhoBAST with the GFP-binding aptamer AP3 facilitates high- and super-resolution imaging of GFP-tagged proteins, which is particularly valuable in view of the widespread availability of plasmids and stable cell lines expressing proteins fused to GFP. The bifunctional aptamers compare favorably with standard antibody-based immunofluorescence protocols, as they are 7-fold smaller than antibody conjugates and exhibit higher bleaching-resistance. We demonstrate the effectiveness of our approach in super-resolution microscopy in secondary mammalian cell lines and primary neurons by RhoBAST-PAINT, an SMLM protein imaging technique that leverages the transient binding of the fluorogenic rhodamine dye SpyRho to RhoBAST.
Zuerst veröffentlicht: 08. August 2024
Gesehen am 06.05.2025